Results of Studying the Efficiency of Chemical Measures Against Weed Vegetation in Sunflower Crops - B. Poida , Valery; M. Falynskov, Eugene; A. Zbrailov, Michael; L. Bushmin, Eugene (KnE Life Sciences, 2021)
This study identified the most effective methods for protecting sunflowers from weeds through the treatment of crops with the herbicides Euro Lightning, Euro Lightning Plus and Express. These options provided substantial protection of sunflowers from weeds such as the cursed thistle, field bindweed, yellow bristle grass, field mustard, frost blite and redroot pigweed. In the fight against ragweed, the herbicides Euro Lightning and Euro Lightning Plus provided excellent action and the herbicide Express provided good results. Variants with the use of the soil herbicides Gezagard and Gardo Gold suppressed yellow bristle grass, field mustard and frost blite, and satisfactorily protected against redroot pigweed. However, they were ineffective against perennial species of weeds (cursed thistle and field bindweed) and ragweed growing in the experimental area. The application of soil herbicides did not influence the growth of sunflower broomrape and plots. The use of the herbicides Euro Lightning and Express helped to reduce the contamination of crops with this type of weed. When processing crops with the herbicide Euro-Lightning Plus, this type of weed was completely absent. Statistical processing of crop data showed a difference in yield in the studied variants. Carrying out weed control measures significantly increased the yield of sunflowers in comparison to control options (without treatment). There was a significant difference in the yield of oilseeds when herbicides intended for application on vegetating plants (Euro Lightning and Express) were used, compared to when the variants of soil herbicides Gezagard and Gardo Gold were used. Keywords: sunflower, weed plants, herbicides, oilseed productivity